Bone Mineral Density and Related Factors in Renal Transplant Recipients, in the North of Iran (Iranian Journal of Kidney Diseases, 2020)
Introduction. Renal transplantation can lead to or be associated with Low bone mineral density (BMD). The aim of this study is evaluation of BMD and related factors in our renal transplant patients. Methods. In this descriptive cross-sectional analytical study, 148 kidney transplant patients from university hospital, were enrolled. BMD of hip and lumbar spine was measured by dual-energy X-ray absorptiometry (DXA) and patients were divided into 3 groups: normal, osteopenia, and osteoporosis; according to T-score. Laboratory parameters and a series of variables were investigated, and the results were compared with BMD findings. Results. In this study, 73 patients (49.3%) had osteopenia and 28 patients (18.9%) were osteoporotic. BMI was significantly lower in the osteoporosis group compared with the normal group (P < .05). Cumulative dose of prednisolone and calcium supplement were higher in osteoporotic group compared with normal group. Conclusion. According to our results, osteoporotic and osteopenia groups have lower BMI that is associated with lower BMD. This can lead to increased risk of bone fractures in the future. Early discontinuation or reduction of prednisolone dose can improve BMD.